Supermagnetic Sugarcane Bagasse Hydrochar for Enhanced Osteoconduction in Human Adipose Tissue-Derived Mesenchymal Stem Cells - Kim, Min (Nanomaterials (Basel), 2020)
Hydrothermally carbonized sugarcane bagasse (SCB) has exceptional surface properties. Looking at the huge amount of SCB produced, its biocompatible nature, cheap-cost for carbonization, and its easy functionalization can give impeccable nano-biomaterials for tissue engineering applications. Herein, sugarcane bagasse was converted into hydrochar (SCB-H) by hydrothermal carbonation. The SCB-H produced was further modified with iron oxide (Fe(3)O(4)) nanoparticles (denoted as SCB-H@Fe(3)O(4)). Facile synthesized nano-bio-composites were characterized by SEM, HR-TEM, XRD, FT-IR, XPS, TGA, and VSM analysis. Bare Fe(3)O(4) nanoparticles (NPs), SCB-H, and SCB-H@Fe(3)O(4) were tested for cytocompatibility and osteoconduction enhancement of human adipose tissue-derived mesenchymal stem cells (hADMSCs). The results confirmed the cytocompatible and nontoxic nature of SCB-H@Fe(3)O(4). SCB-H did not show enhancement in osteoconduction, whilst on the other hand, Fe(3)O(4) NPs exhibited a 0.5-fold increase in the osteoconduction of hADMSCs. However, SCB-H@Fe(3)O(4) demonstrated an excellent enhancement in osteoconduction of a 3-fold increase over the control, and a 2.5-fold increase over the bare Fe(3)O(4) NPs. Correspondingly, the expression patterns assessment of osteoconduction marker genes (ALP, OCN, and RUNX2) confirmed the osteoconductive enhancement by SCB-H@Fe(3)O(4). In the proposed mechanism, the surface of SCB-H@Fe(3)O(4) might provide a unique topology, and anchoring to receptors of hADMSCs leads to accelerated osteogenesis. In conclusion, agriculture waste-derived sustainable materials like “SCB-H@Fe(3)O(44)” can be potentially applied in highly valued medicinal applications of stem cell differentiation.